TÁCH DÒNG VÀ XÁC ĐỊNH TRÌNH TỰ GEN slo CỦA VI KHUẨN Streptococcus pyogenes ĐƯỢC PHÂN LẬP TẠI VIỆT NAM - Võ, Viết Cường; Nguyễn, Thị Hà Giang; Nguyễn, Như Nghĩa; Nguyễn, Văn Minh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CLONING AND SEQUENCING FOR slo GENE OF Steptococcus pyogenes ISOLATED IN VIETNAMStreptococcus pyogenes is a major cause of upper respiratory tract infections such as pharyngitis, tonsillitis. These diseases can cause serious complications, causing high mortality. Antigen streptolysin O (SLO) was used to detect antibodies to streptolysin O (ASLO) in serum of patients with suspected group A Streptococcus. This study was carried out to clone and sequence the slo gene encoding for SLO of pyogenesstrain isolated in Vietnam (Slo_B37). The results revealed that slo gene was cloned and sequenced in size of 1595 nucleotide, with 20 nucleotides differed from NC_002737 fragment on GeneBank and the degree of genetic similarity is 99%. Translated products of the fragment Slo_B37 has differences with sequence of NP_268546 translated from NC_002737 gene in three amino acids at positions: T29M, N34S and T413S.